Analisis Gaya Belajar Siswa Berprestasi di Sekolah Dasar Negeri Sembungharjo 01 Kecamatan Genuk Kota Semarang - Ronald Andrean; Khusnul Fajriyah; Intan Rahmawati (Melati Institute, 2024)
The purpose of this study was to determine the learning styles of high-achieving students at Sembungharjo 01 State Elementary School, Genuk Subdistrict, Semarang City. This research is a qualitative research. Data were collected through observation, interviews, and documentation. The results showed that nine outstanding students at Sembungharjo 01 State Elementary School in Genuk Subdistrict have a combination of visual learning styles, auditorial learning styles, and kinesthetic learning styles. However, each outstanding student has a different learning style tendency. Based on the results of the analysis, it shows that two students have visual learning style tendencies, four students have auditorial learning style tendencies, and three students have kinesthetic learning style tendencies. Complete infrastructure facilities from schools and learning methods used by teachers are factors that influence learning styles and student achievement.